2001
DOI: 10.1046/j.1365-2052.2001.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the GTL2 gene within the callipyge region of ovine chromosome 18

Abstract: The inheritance pattern of the skeletal muscle hypertrophy phenotype caused by the callipyge gene has been characterized as polar overdominance. We hypothesized that this trait may be caused by a gain or loss of gene expression because of the reversible nature of the phenotype in paternal vs. maternal inheritance. Suppression subtraction cDNA probes were made from skeletal muscle mRNA of normal (NN) and callipyge (C(Pat)N(Mat)) animals and hybridized to Southern blots containing bacterial artificial chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 38 publications
(44 reference statements)
4
20
0
Order By: Relevance
“…Our results for MEG3 agree with those previously reported by Charlier et al (2001a) and Bidwell et al (2001) in that there is an increase in maternally expressed MEG3 from alleles carrying the mutation. In the Charlier et al study, MEG3 transcripts were elevated in longissimus dorsi of unaf- PAT sheep, these results together suggest that MEG3 is unlikely to be a direct mediator of the muscle hypertrophy phenotype.…”
Section: Discussionsupporting
confidence: 81%
“…Our results for MEG3 agree with those previously reported by Charlier et al (2001a) and Bidwell et al (2001) in that there is an increase in maternally expressed MEG3 from alleles carrying the mutation. In the Charlier et al study, MEG3 transcripts were elevated in longissimus dorsi of unaf- PAT sheep, these results together suggest that MEG3 is unlikely to be a direct mediator of the muscle hypertrophy phenotype.…”
Section: Discussionsupporting
confidence: 81%
“…However, a potential function for SNP CLPG has been inferred from studies that examined the expression patterns of genes in the DLK1-GTL2 cluster in animals of the four CLPG genotypes. Northern blot analysis of longissimus muscle-derived RNA has demonstrated that the expression of DLK1, GTL2, PEG11, antiPEG11, and MEG8 is altered in a genotype-and muscle-specific manner [5,13]. Specifically, the expression levels of these genes are increased in longissimus muscle from 8-week-old individuals when the CLPG mutation is inherited in cis, yet these genes maintain their exclusive expression from either the paternal or maternal allele [13].…”
Section: The Callipyge (Clpg) Locusmentioning
confidence: 99%
“…The expression patterns of a number of the imprinted genes surrounding the callipyge mutation are dysregulated in affected skeletal muscles (6,7,13,48,69). These genes include Dlk1, Gtl2, Peg11, Peg11as, and Meg8.…”
mentioning
confidence: 98%